The effect of assisted jumping on vertical jump height in elite volleyball players - Sheppard, J. M.; Dingley, A. A.; Janssen, I.; Spratford, W.; Riggs, M.; Chapman, D. W. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Assisted jumping may be useful in training higher concentric movement speed in the propulsive phase of jumping, thereby potentially increasing the jumping abilities of athletes. The purpose of this study was to evaluate the chronic effects of assisted jump training on the counter-movement vertical jump (CMVJ) and spike jump (SPJ) ability in a group of elite volleyball players. Methods Seven junior national team volleyball players (18.0±1.0 years, 200.4±6.7 cm, and 84.0±7.2 kg) participated in this within-subjects cross-over counter-balanced training study. Assisted training involved 3 sessions per week of CMVJ training with 10 kg of assistance, applied through use of a bungee system, whilst normal jump training involved equated volume of unassisted counter-movement vertical jumps. The training intervention period was 5 weeks duration, with a 3 week wash-out separating the training periods. Vertical jump and reach testing for CMVJ and SPJ height were conducted prior to and at the conclusion of each training period. Results Assisted jump training resulted in gains of 2.7±0.7 cm (p<0.01, d=0.21) and 4.6±2.6 cm (p<0.01, d=0.32) for the CMVJ and SPJ respectively, whilst normal jump training did not result in significant gains for either CMVJ or SPJ (p=0.09 and p=0.51, respectively). The changes associated with normal jump training and assisted jump training revealed significant differences in both CMVJ and SPJ (p=<0.03) in favour of the assisted jump condition, and with large effect (CMVJ, d=1.22; SPJ, d=1.31). Discussion/Conclusion It is proposed that assisted jumping may promote the leg extensor musculature to develop force while undergoing an increased rate of muscle shortening. Chronic exposure to this accelerated rate of shortening (in conjunction with more traditional strength and conditioning activities) may have promoted the improvement in jump height of the volleyball players in this study, possibly through a decrease in antagonist co-activation